Cardiovascular regulation through hypothalamic GABA(A) receptors in a genetic absence epilepsy model in rat - ONAT, FİLİZ; GÜLHAN, REZZAN (BLACKWELL PUBLISHING INC, 2002)
Purpose: gamma-Aminobutyric acid (GABA) plays a vital role in both central cardiovascular homeostasis and pathogenesis of epilepsy. Epilepsy affects autonomic nervous system functions. In this study, we aimed to clarify the role of GABA(A) receptors in hypothalamic cardiovascular regulation in a genetically determined animal model of absence epilepsy. Methods: Nonepileptic Wistar rats and genetic absence epilepsy rats from Strasbourg (GAERS) were instrumented with a guide cannula for drug injection and extradural electrodes for EEG recording. After a recovery period, iliac arterial catheters were inserted for direct measurement of mean arterial pressure and heart rate. Bicuculline, a GABA(A)-receptor antagonist, was injected into the dorsomedial (DMH) or posterior (PH) hypothalamic nuclei of nonepileptic control rats or GAERS. Blood pressure, heart rate, and EEG recordings were performed in conscious unrestrained animals. Results: Bicuculline injections into the hypothalamus produced increases in blood pressure and heart rate of both control rats and GAERS. The DMH group of GAERS showed a twofold increase in the blood pressure and the heart rate compared with those of control rats. Pressor responses to bicuculline, when microinjected into the PH, were similar in the nonepileptic animals and GAERS. Conversely, the amplitude of tachycardic responses to the administration of bicuculline into the PH was significantly higher in GAERS compared with those of control rats. Conclusions: The bicuculline-induced increases in blood pressure and heart rate were more prominent when given in the DMH of GAERS. These results indicate an increased GABA(A) receptor-mediated cardiovascular response through the DMH in conscious rats with absence epilepsy.
Keywords: blood pressure; heart rate; absence epilepsy; hypothalamus; rat; AUTONOMIC NERVOUS-SYSTEM; NON-CONVULSIVE EPILEPSY; DORSOMEDIAL HYPOTHALAMUS; EPILEPTOGENIC ACTIVITY; CARDIAC-ARRHYTHMIAS; SUDDEN-DEATH; HEART-RATE; BICUCULLINE; RESPONSES; SEIZURES